The Rights and Aspirations of the Magna Carta - Gibson-Morgan, Elizabeth; Chommeloux, Alexis; SpringerLink (Online service) (Cham : Springer International Publishing(Imprint), 2016)
This book provides an original and multidisciplinary approach on Magna Carta (1215) as a joint heritage, a source of inspiration both for long established democracies and countries which only recently experienced the Rule of Law. Far from simply extolling the virtues associated with Magna Carta, it explores the gaps of the Great Charter. Instead of dealing separately with the historians' and the lawyers' outlooks as two conflicting perspectives, it juxtaposes the views of medievalist and contemporary historians with those of practicing lawyers and law academics, offering readers a thorough yet accessible historic and legal analysis of the charter and its meaning for the citizens of twenty-first century democracies. At a time of the erosion of civil liberties and fundamental rights, The Rights and Aspirations of the Magna Carta provides a rare insight into the 1215 medieval charter and its legacy.
Introduction: Elizabeth Gibson-Morgan and Alexis Chommeloux -- 1. King John, Magna Carta and the Thirteenth-Century English Church; Elizabeth Gemmill -- 2. Magna Carta 1815-2015: Filling up the Gaps; Kenneth O. Morgan -- 3. US Supreme Court v. US Supreme Court: Modern Use of Magna Carta; Geraldine Gadbin-George -- 4. Exploring the Magna Carta and Governmental Immunity Doctrines: The View from the United States; Credence Sol -- 5. A New Magna Carta? The Written Constitution Debate in the United Kingdom; Andrew Blick -- 6 'Omnibus liberis hominibus': The Rights of Refugees, Migrants and Exiles; Alison Harvey) -- 7. Where is Magna Carta Today?; Matthias Kelly -- 8. Magna Carta and the Charter of the European Union; Peter Gjørtler.
Keywords: Europe-History-476-1492.; World history; Law-History.; World politics; Political History